CHANGES IN HEMODYNAMICS IN THE TESTES AND EJACULATES OF ADULT MEN IN CHRONIC DIABETES MELLITUS - Hrytsuliak, B.V.; Hrytsuliak, V.B.; Hlodan О.Ia.; Bielova, N.V.; Dolynko, N.P.; Mykytyn, T.V. (World of Medicine and Biology, 2021)
An analysis was performed of echometric, hemodynamic, histological and laboratory changes in the testes and ejaculate of infertile men aged 22–35 years (the first period of adulthood), who were diagnosed with insulin-dependent diabetes mellitus of moderate severity. It is established that under these conditions, the volume of both testicles probably decreases, hemodynamic parameters in them both within the spermatic cord and under the protein shell decrease, there is a reduction of spermatogenic epithelial cells’ layers in the vast majority of tortuous seminal tubules, the concentration of testosterone in the blood decreases, and in the ejaculate – the total number of sperm, the number of living and actively moving sperm reduces. The number of pathological forms of sperm doubles, and the number of immobile sperm increases by 5 times.